Business Behavior Strategy of IT Companies in Times of War - Kompanets, Nikita Ihorovych (Global Prosperity, 2023)
This article explores critical aspects of the business behavior strategy of information technology (IT) companies in times of war. Considering the instability of the geopolitical situation and increased risks in the context of the Russian-Ukrainian conflict, the article provides valuable insights on maintaining security, adapting to new conditions, altering strategic partnerships and contracts, as well as developing crisis plans and business continuity. The primary focus is on preserving stability and operational continuity of IT companies in the face of global emergencies